MASYARAKAT BILATERAL ISLAM - KHOIRUDDIN NASUTION (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
Hazairin can be classified as a phenomenal Islamic scholar, together with a number of other Islamic scholars, such as Fazlur Rahman from Pakistan, Syahrur from Syria, Fatimah Mernissi from Morocco, Leila Ahmed from Egypt, and several other Islamic scholars. They are called phenomenal Islamic scholars for their formal education are non-Islamic studies, but have contributions and extraordinary and amazing discoveries in the field of Islamic studies. Fazlur Rahman from Pakistan who has the educational background of medical (medicine), Syahrur from Syria who has the formal educational background in civil engineering, Fatimah Mernissi who has the educational background of Sociology, and Leila Ahmed who has the formal education in History at the Universiry of Cambridge, and several other Islamic scholars. The formal educational background of Hazairin is on law, especially Customary Law and Social -Anthropology (Ethnology). However, his studies on the field of Islamic law are very admirable. What has been found by Hazairin can be classified as an invention, not just a development or an improvement. One of Hazairin's remarkable findings is that Islam emerges to build a community based on the bilateral family. His conclusion is contrary to the formulation and conclusion of other scholars and the most mulim in general that Islam emerges to build the community based on patrilineal family. This article is a description of Hazairin's brilliant theory. Keywords: bilateral Islamic society, hazairin, customary law